Association between Neutrophil-to-Lymphocyte Ratio and Gut Microbiota in a Large Population: a Retrospective Cross-Sectional Study. Issue 1 (December 2018) - Yoon, Hee-Young; Kim, Han-Na; Lee, Su; Kim, Soo; Chang, Yoosoo; Ryu, Seungho; Shin, Hocheol; Kim, Hyung-Lae; Lee, Jin
Abstract Gut microbiota and blood neutrophil-to-lymphocyte ratio (NLR) are associated with systemic inflammation; however, data on the association between gut microbiota and NLR are lacking. We investigated the association between gut microbiota and NLR. A total of 1, 309 subjects who had available data on NLR and 16 S rRNA sequencing of gut microbiota were included in this study. They were grouped according to NLR quartile (Q) as follows: lower Q (n = 328, <25% of NLR range), middle 2Q (n = 653, ≥25% to <75%) and upper Q (n = 328, ≥75%). The diversity and composition of the human gut microbiota in the groups were calculated. The phylogenetic diversity of gut microbiota in the lower group was significantly higher than in the middle 2Q group (P = 0.040). The beta-diversity was significantly different among the three groups (P = 0.043), between the lower and middle 2Q groups (P = 0.029), and between the lower and upper groups (P = 0.026).Bacteroides eggerthii showed a positive correlation with NLR (q = 0.015). The diversity and composition of the gut microbiome were different between the NLR groups. Particularly, patients with a lower NLR had a greater diversity of gut microbiota.